221. Comparison of dental antibiotic prescribing between Australia, England, the United States and British Columbia in 2017. (31st December 2020) - Teoh, Leanne; Thompson, Wendy; Hubbard, Colin; Patrick, David M; Marra, Fawziah; Mamun, Abdullah A; Campbell, Allen; Suda, Katie
Abstract: Background: Antibiotic resistance is recognised as a major public health burden. Dentists overprescribe antibiotics and prescribe for unnecessary indications. Tracking and investigating prescribing practices by healthcare professionals provides insights needed to inform targeted antibiotic stewardship interventions. It is unclear how dental antibiotic prescribing patterns differs between countries. The aim of this study was to compare antibiotic prescribing by dentists in Australia, England the United States (US) and British Columbia (BC). Methods: This was a cross-sectional study of dispensed dental antibiotic prescriptions between January 1 and December 31, 2017, from Australia, England, US and BC. Dispensed dental antibiotic prescriptions included those from outpatient pharmacies and healthcare settings. Outcome measures included the proportion of dental antibiotic prescriptions by location and prescribing rates by population. Results: English dentists prescribed 1.6 times more antibiotics than those in Australia, and dentists in BC and US prescribed around twice more than Australian dentists. (Australia: 33.2 prescriptions/1000population; England: 53.5 prescriptions/1000population; US: 72.6 prescriptions/1000 population; BC: 65.0 prescriptions/1000 population). The types of antibiotics prescribed were similar across all countries, where penicillins were the predominant class prescribed (66.8–80.5% of antibiotic prescriptions). US dentists and dentists in BC prescribed more clindamycin compared to the dentists in other countries. Conclusion: Dentists in the US, England and BC prescribed at relatively higher rates than Australian dentists. The findings from this study should initiate an evaluation by dentists of their prescribing practices and responsibilities regarding their contribution towards antibiotic resistance. Further investigations can be aimed at determining country-specific factors that influence dental antibiotic prescription. Disclosures: Leanne Teoh, BDSc(Hons) BPharm(Hons), Australian Government Research Training Program Scholarship (Other Financial or Material Support, Scholarship awarded for the PhD candidature)